Assessing seventh-grade students' computational thinking skills through problem-based learning: Focus on integer addition and subtraction - Hapizah, Hapizah; Mariela, Anadia Muli; Mulyono, Budi (Journal of Honai Math, 2024)
Computational thinking is a crucial skill that facilitates problem-solving for students. Recognizing its importance, the PISA 2021 framework incorporates computational thinking to enhance problem-solving and mathematical reasoning abilities. However, the proficiency of students in computational thinking remains low in Indonesia due to its infrequent integration into the curriculum. This study aims to evaluate students' computational thinking skills based on the indicators of decomposition, pattern recognition, abstraction, and algorithmic thinking following the implementation of computational thinking-based learning using the Problem-based Learning (PBL) model, specifically on integer addition and subtraction. The research involved 28 seventh-grade students from SMP Negeri 54 Palembang during the first semester of the 2023/2024 academic year. Data were collected through tests and interviews. The findings indicate that students' computational thinking skills are at a medium level. Furthermore, the study examines students' abilities concerning specific computational thinking indicators. It underscores the impact of computational thinking-based learning in enhancing students' ability to design and develop structured and systematic problem-solving strategies.